Aspirin and fracture risk: a systematic review and exploratory meta-analysis of observational studies. Issue 2 (20th February 2020) - Barker, A L; Soh, Sze-Ee; Sanders, Kerrie M; Pasco, Julie; Khosla, Sundeep; Ebeling, Peter R; Ward, Stephanie A; Peeters, Geeske; Talevski, Jason; Cumming, Robert G; Seeman, Ego; McNeil, John J
Abstract : Objectives: This review provides insights into the potential for aspirin to preserve bone mineral density (BMD) and reduce fracture risk, building knowledge of the risk-benefit profile of aspirin. Methods: We conducted a systematic review and exploratory meta-analysis of observational studies. Electronic searches of MEDLINE and Embase, and a manual search of bibliographies was undertaken for studies published to 28 March 2018. Studies were included if: participants were men or women aged ≥18 years; the exposure of interest was aspirin; and relative risks, ORs and 95% CIs for the risk of fracture or difference (percentage or absolute) in BMD (measured by dual energy X-ray absorptiometry) between aspirin users and non-users were presented. Risk of bias was assessed using the Joanna Briggs Institute Critical Appraisal Checklists for observational studies. Pooled ORs for any fracture and standardised mean differences (SMDs) for BMD outcomes were calculated using random-effects models. Results: Twelve studies met the inclusion criteria and were included in the meta-analysis. Aspirin use was associated with a 17% lower odds for any fracture (OR 0.83, 95% CI 0.70 to 0.99; I 2 =71%; six studies; n=511 390). Aspirin was associated with a higher total hip BMD for women (SMD 0.03, 95% CI −0.02 to 0.07; I 2 =0%; three studies; n=9686) and men (SMD 0.06, 95% CI −0.02 to 0.13, I 2 =0%; two studies; n=4137) although these associations were not significant. Similar results were observed for lumbar spine BMD in women (SMD 0.03, 95% CI −0.03 to 0.09; I 2 =34%; four studies; n=11 330) and men (SMD 0.08; 95% CI −0.01 to 0.18; one study; n=432). Conclusions: While the benefits of reduced fracture risk and higher BMD from aspirin use may be modest for individuals, if confirmed in prospective controlled trials, they may confer a large population benefit given the common use of aspirin in older people.